Night road [large type] : a novel of suspense - DuBois, Brendan (Thorndike Press, 2016)
Dishonorably discharged from a top-notch covert Coast Guard position, Zach Morrow is left with almost nothing. So when Homeland Security offers an honorable discharge and full pension in exchange for his help, Zach agrees. All he has to do is get information on an old classmate.